A Revision of the Deep-Sea Genus Axiokebuita Pocklington and Fournier, 1987 (Annelida: Scalibregmatidae) - Parapar, Julio; Gambi, Maria Cristina; Rouse, Greg W. (Italian Journal of Zoology, 2011)
[Abstract] The deep-sea genus Axiokebuita (Annelida, Scalibregmatidae) has hitherto been considered to contain two species, Axiokebuita minuta (Hartman, 1967) and Axiokebuita millsi Pocklington and Fournier, 1987, each rarely recorded in the literature and both supposedly having bipolar distributions. From the study of some types, other museum collection material, plus newly collected specimens from the slope depths of the Bellingshausen Sea and off the Antarctic Peninsula (Antarctica), Iceland and Iberian Peninsula, as well as from hydrothermal vents of the southeastern Pacific Ocean, the taxonomic history of the genus is revisited. Based on the results of this study, the features traditionally used to distinguish between the two species are actually the same in both. Therefore, A. millsi is proposed to be synonymised with A. minuta, which is redescribed and considered the only valid species of the genus, leaving Axiokebuita monotypic. Two previously unnoticed body sensory structures, i.e. a ciliated neck organ and a prostomial depression, were observed under scanning electron microscopy. United States. National Science Foundation; OCE- 0241613 United States. National Science Foundation; OCE-0350554 Ministerio de Educación y Ciencia; GLC2004–01856/ANT